IL‐18Rα‐deficient CD4+ T cells induce intestinal inflammation in the CD45RBhi transfer model of colitis despite impaired innate responsiveness. Issue 6 (6th May 2016) - Holmkvist, Petra; Pool, Lieneke; Hägerbrand, Karin; Agace, William W.; Rivollier, Aymeric
Abstract : Holmkvist et al. dissected the involvement of IL‐18R signaling in the differentiation of CD4 + effector T cells and in their TCR‐independent innate responsiveness in the intestinal mucosa. Although IL‐18R signaling is required for the optimal generation and/or maintenance of IFN‐γ‐producing CD4 + T cells and critical for their innate responsiveness, it is dispensable for the development of T‐cell‐mediated colitis. Abstract : IL‐18 has been implicated in inflammatory bowel disease (IBD), however its role in the regulation of intestinal CD4 + T‐cell function remains unclear. Here we show that murine intestinal CD4 + T cells express high levels of IL‐18Rα and provide evidence that IL‐18Rα expression is induced on these cells subsequent to their entry into the intestinal mucosa. Using the CD45RB hi T‐cell transfer colitis model, we show that IL‐18Rα is expressed on IFN‐γ +, IL‐17 +, and IL‐17 + IFN‐γ + effector CD4 + T cells in the inflamed colonic lamina propria (cLP) and mesenteric lymph node (MLN) and is required for the optimal generation and/or maintenance of IFN‐γ‐producing cells in the cLP. In the steady state and during colitis, TCR‐independent cytokine‐induced IFN‐γ and IL‐17 production by intestinal CD4 + T cells was largely IL‐18Rα−dependent. Despite these findings however, IL‐18Rα−deficient CD4 + T cells induced comparable intestinal pathology to WT CD4 + T cells. These findings suggest that IL‐18‐dependent cytokine induced activation of CD4 + T cells is not critical for the development of T‐cell‐mediated colitis.